Spectrum of Renal Stones Composition; Chemical Analysis of Renal Stones - Bangash, Kashif; Shigri, Farwa; Jamal, Ahsan (International Journal of Pathology, 2018)
Background: Pakistan has probably one of the highest incidences of renal stone disease.Objective: The study aimed to qualitatively analyze the uroliths in Pakistani population and evaluate the predominantconstituent present in them.Materials & Methods: The study included 232 uroliths obtained by surgical intervention of Urolithiasis patientspresenting to Pakistan Institute of Medical Sciences. The stones were analyzed by DiaSys analysis kit.Results: Males were more prone to renal stone disease (M:F is 2.7:1) and mostly affected the working age group.All the stones contained oxalate (100%) and calcium was present in 99.5%. This was followed by uric acid (40.9%),phosphate (25%), ammonium (7.3%), magnesium (4.3%) and cystine (0.86%).Conclusion: Calcium Oxalate was the most predominant chemical composition in stones of 203 patients (87.5%)followed by uric acid, struvite and calcium phosphate stones in 15 (6.5%), 10 (4.3%) and 3 (1.29%) respectively.